Biograficzna książka albumowa "Jan Paweł II. Dowody świętości" jako tekst kultury popularyzujący postać Papieża = The biographical book album "John Paul II. The evidence of sanctity" as a text of culture popularizing Pope`s figure - Klimek, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this article is to show the biographical album book "John Paul II. The evidence of sanctity" presenting the private life of Charles Wojtyla and his pontifical service, which was published in 2006 as an appendant to "Fact" newspaper.
Keywords: Jan Paweł II, papież (1929-2005); John Paul II; biografia; biography